Faktor-faktor yang Berpengaruh Terhadap Penjualan Padi dengan Sistem Tebasan di Subak Babakan Desa Sambangan Kecamatan Sukasada Kabupaten Buleleng - RESIANA, KETUT; ASTITI, NI WAYAN SRI; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Influencing Factors Toward Rice Selling with Rice Slash System in Subak Babakan, Sambangan Village, Sukasada Subdistrict, Buleleng Regency The purpose of this study was to determine the influenced factors such as; age, education, farming experience, number of family dependents, and land tenure were affected farmers for making decision for choosen rice sold with slash system and their bargaining position within sold grain with the slash system. This research was done in Subak Babakan, Sambangan Village, Sukasada Sub-District, Buleleng Regency. The subjek was 36 farmers of Subak Babakan. The land ownership per household was on average 0.80 hectares. Meanwhile, in the negotiation of crop yields with the slashing system, the bargaining position of farmers were still very low due to a lack of knowledge and negotiation skills in determining the price of grain. The results showed that some the factors showed positive effect. Those effect were age, education background, farming experience, number of family dependents and land tenure has significantly effect. The statistical analysis result showed t-count > t-table. The data also showed the farmers bargaining position within sold grain in the slash system was still very low. This due to lack of knowledge and skills in negotiation and determination of the price of grain.